Urban Graveyard in Spatial Change Perspective - Dilahur, D (Universitas Muhammadiyah Surakarta, 1990)
The growth of urban population tends to increase constantly but some towns show faster growth than others. Ultimately the urban area extends tremendously, and a new urban environment is created. Graveyard is one phenomenon that an not be neglected from this process. Duc to their strategic locations, some portions have undergone changes in economic, social, and environment values. For the time being lands used for graveyards are constantly increasing. The competition with other uses can not be avoided anyway and land conservation must be carried out concomitantly.